2008
DOI: 10.1086/590129
|View full text |Cite
|
Sign up to set email alerts
|

Weathering Corruption

Abstract: Could bad weather be responsible for U.S. corruption? Natural disasters create resource windfalls in the states they strike by triggering federally provided natural-disaster relief. By increasing the benefit of fraudulent appropriation and creating new opportunities for such theft, disaster-relief windfalls may also increase corruption. We investigate this hypothesis by exploring the effect of disaster relief provided by the Federal Emergency Management Agency (FEMA) on public corruption. The results support o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
133
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(144 citation statements)
references
References 6 publications
10
133
0
1
Order By: Relevance
“…Further analysis reveals that though Louisiana has a colorful history of corruption, so, too, do other states with a high occurrence of natural disasters. Leeson and Sobel (2006) show that Louisiana, Mississippi, and Florida are the most politically corrupt states and are also the states hardest hit by natural disasters. Corruption notwithstanding, citizens of the United States, and specifically the residents of New Orleans, were failed by the very systems designed to assist them-systems funded using their tax dollars.…”
Section: The Colorful Past Of New Orleansmentioning
confidence: 99%
“…Further analysis reveals that though Louisiana has a colorful history of corruption, so, too, do other states with a high occurrence of natural disasters. Leeson and Sobel (2006) show that Louisiana, Mississippi, and Florida are the most politically corrupt states and are also the states hardest hit by natural disasters. Corruption notwithstanding, citizens of the United States, and specifically the residents of New Orleans, were failed by the very systems designed to assist them-systems funded using their tax dollars.…”
Section: The Colorful Past Of New Orleansmentioning
confidence: 99%
“…Public sector corruption is one of the major issues of concern when considering the interaction between politics and economics 3 (e.g., Glaeser & Saks 2006;Gokcekus 2008;Apergis et al 2010;Dreher & Schneider 2010;Escaleras et al 2010;Johnson et al 2011;Swaleheen 2011). Natural disasters possibly generate an incentive to practice corruption, which is generally defined as the use of public office for private gain (Boettke et al 2007;Leeson & Sobel 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, public employees were accused of soliciting bribes from relief-funded contractors and of overbilling the government (Leeson & Sobel 2008). Similarly, the misuse of reconstruction funds was revealed in the case of the Great East Japan Earthquake, when it was reported that "a special account budget to fund the reconstruction of communities devastated by the 3/11 earthquake, tsunami, and nuclear disasters has been used to pay for unrelated projects" (Japan Times 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations